Relationship between Serum Cytokeratin-18, Control Attenuation Parameter, NAFLD Fibrosis Score, and Liver Steatosis in Nonalcoholic Fatty Liver Disease - Kosasih, Sumitro (Int J Hepatol, 2018)
BACKGROUNDS: The aim of this study was to appraise the relationship between serum fragmented cytokeratin-18(CK-18), controlled attenuation parameter (CAP), and liver steatosis assessed by ultrasound (US) in nonalcoholic fatty liver disease (NAFLD) patients. METHODS: Patients who underwent abdominal US were recruited, followed with measurement of CAP using Fibroscan(®) and serum fragmented CK-18 using enzyme-linked immunosorbent assay. The degree of liver steatosis assessed by US was categorized into mild (S1), moderate (S2), and severe (S3). RESULTS: A total of 109 patients were included in our study. CAP and fragmented CK-18 level were significantly correlated with liver steatosis grade with r(s) = 0.56 and 0.68, p=0.001, respectively. NAFLD Fibrosis Score was poorly correlated with liver steatosis grade (r(s)=-0.096, p=0.318). Using fragmented CK-18 level, area under receiver operating characteristic (AUROC) curves for S≥2 and S≥3 were excellent (0.82 and 0.84, respectively). Using CAP, AUROC curves for detection of S≥2 and S≥3 were good (0.76, 0.77, respectively). We also proposed cut-off value of CAP to detect S≥2 and S≥3 to be 263 and 319db/m, respectively, and fragmented CK-18 level to detect S≥2 and S≥3 (194 and 294 U/L, respectively). CONCLUSIONS: Both the fragmented CK-18 level and the CAP, but not NAFLD Fibrosis Score, were well correlated with hepatic steatosis grade as assessed by US.